PELATIHAN BUDIDAYA MAGGOT SEBAGAI BIOKONVERSI LIMBAH ORGANIK DAN PEMASUKAN TAMBAHAN BAGI MASYARAKAT - Siswadi, Siswadi; Fudoly, Dicky Thopal; Citra, Melia (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2024)
Due to the lack of temporary disposal sites (TPS), the village of Tanjungbungin faces problems in managing waste. The study looks at how the cultivation of Maggot Black Soldier Fly (BSF) in Tanjungbungin Village, Pakisjaya District, Karawang District, West Java, can be used as a creative way to manage organic waste and make money. With the aim of providing training and understanding to villagers about the economic potential of BSF maggot cultivation, this community service program will take place on July 5, 2021 and involve 46 villagers. The program introduces maggot breeding techniques and their use as an alternative feed for livestock. The results of the research show that the amount of organic waste in the villages has decreased, and the public has become more aware of the economic value of biological waste. The price of dry and processed maggot increased from Rs 8.000 to Rs 30,000–Rp 40,000/kg. This study shows a link between local economic development and sustainable waste management. It also provides information about the cultivation of BSF maggot as a useful technique to reduce organic waste and increase the income of the Tanjungbungin Village community.